2020
DOI: 10.1111/1759-7714.13303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of apatinib combined with EGFR‐TKI in the treatment of chronic progression after EGFR‐TKI treatment in non‐small cell lung cancer (ChiCTR1800019185)

Abstract: This clinical trial (ChiCTR1800019185) is designed to be an open‐label, prospective, single‐center, single arm exploratory research study. The study will recruit non‐small cell lung cancer patients (NSCLC) with slow progression after first‐line treatment with EGFR‐TKI drugs. Slow progression will be confirmed by the presence of serum carcinoembryonic antigen or imaging evaluation. The primary aim is to assess progression‐free survival after EGFR‐TKIs treatment combined with apatinib 250 mg once daily. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…One of the most important growth factors is VEGF. VEGF can bind to receptors VEGFR-1 and VEGFR-2 on the surface of vascular endothelial cells, induce receptor dimerization, and phosphorylate the receptors' intracellular tyrosine kinase structure domain activation, activate PLC-g/PKC, RAS/MAPK and PI3K/AKT signaling pathways, induce endothelial cell proliferation, migration and cell survival (48)(49)(50)(51), and ultimately lead to tumor angiogenesis (52). At the same time, VEGF is also known to play a key role in the early stages of metastases (53)(54)(55).…”
Section: Combined Application Of Egfr-tki and Anti-vascular Endotheli...mentioning
confidence: 99%
“…One of the most important growth factors is VEGF. VEGF can bind to receptors VEGFR-1 and VEGFR-2 on the surface of vascular endothelial cells, induce receptor dimerization, and phosphorylate the receptors' intracellular tyrosine kinase structure domain activation, activate PLC-g/PKC, RAS/MAPK and PI3K/AKT signaling pathways, induce endothelial cell proliferation, migration and cell survival (48)(49)(50)(51), and ultimately lead to tumor angiogenesis (52). At the same time, VEGF is also known to play a key role in the early stages of metastases (53)(54)(55).…”
Section: Combined Application Of Egfr-tki and Anti-vascular Endotheli...mentioning
confidence: 99%
“…Soluble cytokines have been reported to prevent viral replication by inducing the expression of many interferon-stimulated genes, thereby activating antiviral and antiproliferative states [ 23 ]. It has been reported that the binding of VEGFR can promote the growth of blood vessels in lung cancer [ 24 ], thereby affecting tumor proliferation. In addition, VEGFR was recently found to be highly expressed during inflammation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case 7, reported by Iezumi et al (10), CSCLC patients received a combined chemotherapy regimen of cisplatin and irinotecan hydrochloride and received radiotherapy for metastasis and recurrence in the forearm. For CSCLC patients with EGFR mutations, use currently mature epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors and other drug-related molecular targeted therapies to exert anti-tumor activity (17,18). Some researchers believe that pure SCLC and CSCLC have similar clinical manifestations and that the operation outcomes of both in a limited stage are similar.…”
Section: Discussionmentioning
confidence: 99%